Long Hour’s Effects on Work Life Balance and Satisfaction: A Case of Nepalese Commercial Banks - Lama, Dawa Dolma (Nepalese Journal of Business, 2025)
This study examines long hour’s effects on work life balance and satisfaction: A case of Nepalese commercial banks. Employee Satisfaction is the dependable variables. The independent variables are over time working hour, work family balance, job stress, leave policy and mental health. The study used primary sources of data. The study is based on primary data with 128 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the impact of long hour effects on work life balance and satisfaction in case of Nepalese commercial banks. The study shows that overtime working hour is negatively correlated to employee satisfaction. It means that increase in over time working hour leads to decrease in employee satisfaction. Similarly, work family balance is positively correlated to employee satisfaction. It means that maintaining work family balance can increase employee satisfaction. Furthermore, job stress is negatively correlated to employee satisfaction. It reveals that increase in job stress leads to decrease in employee satisfaction. Moreover, leave policy is positively correlated to Employee satisfaction. It indicates that as increase in leave policy leads to increase in employee satisfaction. In addition, there is a positive relationship between mental health and employee satisfaction which indicates that increase in mental health leads to increase in employee satisfaction.